The Minimum Merrifield–Simmons Index of Unicyclic Graphs with Diameter at Most Four - Kun Zhao; Shangzhao Li; Shaojun Dai (Journal of Mathematics)
The Merrifield–Simmons index iG of a graph G is defined as the number of subsets of the vertex set, in which any two vertices are nonadjacent, i.e., the number of independent vertex sets of G. In this paper, we determine the minimum Merrifield–Simmons index of unicyclic graphs with n vertices and diameter at most four.